Distribution and numbers of moulting non-breeding Greylag Geese in Norway - Follestad, Arne; Nygård, Torgeir; Røv, Nils; Larsen, Bjørn Harald (Wildfowl, 1988)
This paper reviews the status of moulting nonbreeding populations of Greylag Geese in Norway. The moulting population is now estimated to be a minimum of 22,000 geese, and the data indicate a substantial population increase in central parts of the moulting area. The two main moulting grounds are the archipelagos of Froya and Vega. This new estimate is discussed in relation to the breeding populations of Greylags in Norway. Although geese generally move to the north to moult, this pattern seems to be reversed in northern parts of Norway.